∫ 0 2 π [ ( cot x ) lo g ( sin x ) lo g 4 ( cos x ) ] d x
For positive integers a , b , c , d , e , f , the above integral can be stated in the form of
b a ζ c ( d ) − f π e
Where a , b are coprime. Find f − e − d − c − b − a .
Details and Assumptions
This problem is inspired by this
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
The answer is 1 6 3 ζ 2 ( 3 ) − 3 3 6 0 π 6
∫ 0 2 π [ ( cot x ) lo g ( sin x ) lo g 4 ( cos x ) ] d x = 2 6 1 ∫ 0 1 x lo g x lo g 4 ( 1 − x ) d x
2 6 1 ∫ 0 1 x lo g x lo g 4 ( 1 − x ) d x = 2 6 1 ∫ 0 1 1 − x lo g ( 1 − x ) lo g 4 ( x ) d x
Let,
I s = ∫ 0 1 1 − x lo g ( 1 − x ) lo g s ( x ) d x
H n − H n − 1 = n 1
∑ n = 1 ∞ H n x n − x ∑ n = 1 ∞ H n − 1 x n − 1 = ∑ n = 1 ∞ n x n
∴ n = 1 ∑ ∞ H n x n = − 1 − x lo g ( 1 − x )
where, H 0 = 0
I s = − n = 1 ∑ ∞ H n ∫ 0 1 x n lo g s ( x ) d x
Now, ∫ 0 1 x n d x = n + 1 1
Differentiating above result with respect to n ,s times,
∫ 0 1 x n lo g s ( x ) d x = ( − 1 ) s ( n + 1 ) s + 1 s !
∴ I s = ( − 1 ) s + 1 s ! n = 1 ∑ ∞ ( n + 1 ) s + 1 H n
I s = ( − 1 ) s + 1 s ! n = 0 ∑ ∞ ( n + 1 ) s + 1 H n + 1 − ( n + 1 ) s + 2 1
I s = ( − 1 ) s + 1 s ! ( n = 1 ∑ ∞ ( n ) s + 1 H n − ζ ( s + 2 ) )
Now ,we use ,
n = 1 ∑ ∞ ( n ) q H n = ( 1 + 2 q ) ζ ( q + 1 ) − 2 1 k = 1 ∑ q − 2 ζ ( k + 1 ) ζ ( q − k )
Now putting all values together,we get the answer.Proof for above identity can be found here
The solution to this problem is taken from Mr.Tunk-Fey Ariawan's solution to this problem